Analisis perlakuan Pajak Pertambahan Nilai bagi wajib pajak setelah dikukuhkan sebagai Pengusaha Kena Pajak pada PT Grand Lotus Reridence (Developer) di Bitung - Ong, Karina Theresia; Sabijono, Harijanto; Kapojos, Peter Marshall (Yayasan Widyantara Nawasena Raharja, 2025)
Value Added Tax (VAT) is a major source of state revenue and is imposed on the consumption of taxable goods and services. This study aims to analyze the calculation, recording, and reporting of VAT after the confirmation of PT Grand Lotus Residence in Bitung as a Taxable Entrepreneur (PKP). The research adopts a qualitative method through interviews and documentation. The results show that VAT calculation and recording have been carried out in accordance with Law No. 7 of 2021 and generally accepted accounting principles. However, VAT reporting was not fully compliant due to delays in filing during January–March 2024, which led to administrative penalties. These findings emphasize the importance of accurate documentation, timely reporting, and strengthened coordination between companies and accounting service providers to ensure tax compliance and minimize sanctions.